An analysis of the psychometric properties of the medication safety competence scale in Turkish - Ayşe Aydinli; Kamuran Cerit (BMC, 2024)
Abstract Purpose Considering the key roles and responsibilities of nurses in ensuring medication safety, it is necessary to understand nurses' competence in medication safety. Therefore, it was aimed to introduce a scale evaluating the medication safety competence of nurses into Turkish and to contribute to the literature by determining the medication safety competence levels of nurses. Methods A methodological and descriptive research design was utilised. The population consisted of nurses in Turkey, and the sample comprised 523 nurses who volunteered to participate. Results The content validity index of the scale was 0.98, and the scale showed a good fit (χ2/df = 3.00, RMSEA = 0.062). The Cronbach's alpha coefficient of the scale was 0.97, indicating high reliability. The mean score was 4.12, which was considered high. Participants who were 40 years old or above, married, and graduates of health vocational schools or postgraduate programs, along with those who had received medication safety training, had higher medication safety competence scores. Conclusion This study presents strong evidence that the Turkish version of the Medication Safety Competency Scale is valid and reliable when administered to nurses. The participants in this study had high levels of medication safety competence.